BLOOD BIOCHEMISTRY - Fatima Sharipovna Nazarova; Abdurakhimova Sevinch (Web of Journals Publishing, 2025)
Blood man organism internal environment is considered and, in the body, many biochemical processes done on the rise participating environment is considered. Blood biochemistry to study important importance profession Blood main structural parts blood plasma and shaped from elements organization found. This indicator hematocrit indicator is considered.